Uterine activity in labour and the risk of neonatal encephalopathy: a case control study. (July 2022) - Reynolds, Adam J.; Murray, Michelle L.; Geary, Michael P.; Ater, Stewart B.; Hayes, Breda C.
Highlights: Increased uterine contraction rates in labour are associated with the risk of HIE. That risk is further elevated when combined with slow cervical dilation. The ability of these factors to predict HIE was not superior to FHR analysis. Abstract: Objective: To determine the relationship between intrapartum contraction frequency, rest interval duration, and cervical dilation speed and the risk of neonatal hypoxic-ischemic encephalopathy (HIE). Study Design: This was a retrospective case-control study conducted in a maternity hospital in Dublin, Ireland. Babies born without major congenital anomalies between September 2006 and November 2017 at ≥ 35 + 0 weeks' gestational age were eligible. Cases were diagnosed with moderate-severe HIE. The controls were the first eligible baby born before and after each case with normal Apgar scores and not admitted to the neonatal unit. Intrapartum uterine activity was assessed by automated analysis of external tocography recordings. Cervical dilation was assessed by linear interpolation between vaginal examination measurements. The speed of cervical dilation was expressed as the times from 4 to 6 cm, >6 cm to the start of pushing, and from pushing to delivery. Results: Intrapartum tocographs results were available in 49 of 88 cases and 121 of 176 controls. The median contraction rate in cases was 7.7 (Interquartile range [IQR]: 6.6–9.0) compared to 7.0 in controls (IQR: 6.2–7.9) (p = 0.021). The median rest interval duration was 56 s (IQR: 38–76) in cases and 62 s (IQR: 50–79) in controls (p = 0.058). Cases took longer to progress from > 6 cm to the start of pushing (cases: 02:58 [01:14–04:49], controls: 01:48 [00:51–03:34], p = 0.020) and from pushing to delivery (cases: 00:34 [00:24–01:10], controls: 00:27 [00:13–00:56], p = 0.036). Conclusions: Higher contraction frequencies and slower progress towards the end of labour are both independently associated with the risk of moderate-severe HIE. Inter-contraction rest interval duration as measured by external tocography does not provide additional accuracy.